From interpretation to refutation of marxism. On Leszek Nowak’s non-marxian historical materialism - Brzechczyn, Krzysztof (Hybris, 2017)
The aim of this article is to outline the theory of a historical process developed within the framework of the Poznań School of Methodology, mainly by Leszek Nowak and a team of his co-workers. In the first part of the paper, the meta-philosophical and meta-theoretical assumptions of Poznań school are reconstructed and juxtaposed with the relevant assumptions of Western analytical Marxism. In the central part of the paper, the main ideas of adaptive reconstruction of historical materialism and non-Marxian historical materialism are presented. In its final part, some problems of reception of Leszek Nowak’s theory of historical process in Polish People’s Republic and the Third Republic are discussed.